Nociceptive processing of elite athletes varies between sport-specific loads: an EEG-based study approach - Dreismickenbecker, E.; Fleckenstein, J.; Walter, C.; Enax-Krumova, E. K.; Fischer, M. J.; Kreuzer, M.; Zinn, S.; Anders, M. (Medicine & Science in Sports & Exercise, 2024)
Introduction For the downstream nociceptive processing of elite athletes recent studies indicate that athletes probably tolerate more pain as compared to a normally active population. Phenotyping the nociceptive processing of athletes in different types of endurance sports can provide insight into training-specific effects, which may help in understanding the long-term effects of specific exercise.